1987
DOI: 10.1126/science.3492044
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Wound Healing Enhanced by Transforming Growth Factor-α and Vaccinia Growth Factor

Abstract: Epidermal regeneration following middermal injuries to skin requires both proliferation and migration of keratinocytes. Epidermal growth factor (EGF) stimulates the proliferation of keratinocytes in culture, and topical administration of EGF accelerates epidermal regeneration of partial thickness burns or split-thickness incisions in vivo. Transforming growth factor-alpha (TGF-alpha) and vaccinia growth factor (VGF) have substantial sequence homology with EGF, and all appear to bind to the same receptor protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
116
0
3

Year Published

1988
1988
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(122 citation statements)
references
References 20 publications
3
116
0
3
Order By: Relevance
“…4) demonstrating that both proteins are specific components of the JUN-dependent mitogenic program. In contrast to SDF-1 and PTN a number of other factors, such as EGF, TGFα and bFGF, which were shown to promote keratinocyte proliferation (Schultz et al, 1987;O'Keefe et al, 1988;Marchese et al, 1990), were not, or only weakly able to rescue the proliferation defect of keratinocytes in Jun -/-fibroblast co-cultures (see supplementary material Fig. S3), suggesting that only a subset of mitogenic cytokines is able to exhibit proliferationpromoting activity in this system.…”
Section: Discussionmentioning
confidence: 99%
“…4) demonstrating that both proteins are specific components of the JUN-dependent mitogenic program. In contrast to SDF-1 and PTN a number of other factors, such as EGF, TGFα and bFGF, which were shown to promote keratinocyte proliferation (Schultz et al, 1987;O'Keefe et al, 1988;Marchese et al, 1990), were not, or only weakly able to rescue the proliferation defect of keratinocytes in Jun -/-fibroblast co-cultures (see supplementary material Fig. S3), suggesting that only a subset of mitogenic cytokines is able to exhibit proliferationpromoting activity in this system.…”
Section: Discussionmentioning
confidence: 99%
“…After poration the cells were exposed to 5 mM glucose with or without 5 mM glucosamine for 3 atherogenesis. TGFa is normally found in arterioles (4) and is mitogenic for the arterial endothelium (18) (26), that do exhibit biologic activities toward vascular cells (27). Insulin did not, however, affect the transcription of TGFa in the aortic smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…ErbB signaling plays a very important role in the reepithelialization of skin wounds, as evidenced by acceleration of burn or partial-thickness wound healing by epidermal growth factor (EGF) (Brown et al, 1989), transforming growth factor-␣ (TGF-␣) (Schultz et al, 1987), heparin-binding EGF-like growth factor (HB-EGF) (Cribbs et al, 1998), and epiregulin (Draper et al, 2003). Corneal wound healing also is markedly inhibited after treatment with ErbB receptor tyrosine kinase inhibitors (RTKIs) (Nakamura et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These events lead to activation of multiple signal transduction pathways via Src homology 2 (SH2)-and phosphotyrosine binding (PTB)-domain containing cytoplasmic proteins, ultimately affecting many cellular functions, including cell migration, proliferation, and differentiation (Hubbard et al, 1998;Hackel et al, 1999). We and others have demonstrated that human skin expresses ErbB1, ErbB2, and ErbB3, but little or no ErbB4 (Press et al, 1990;Prigent et al, 1992;De Potter et al, 2001;Stoll et al, 2001).ErbB signaling plays a very important role in the reepithelialization of skin wounds, as evidenced by acceleration of burn or partial-thickness wound healing by epidermal growth factor (EGF) (Brown et al, 1989), transforming growth factor-␣ (TGF-␣) (Schultz et al, 1987), heparin-binding EGF-like growth factor (HB-EGF) (Cribbs et al, 1998), and epiregulin (Draper et al, 2003). Corneal wound healing also is markedly inhibited after treatment with ErbB receptor tyrosine kinase inhibitors (RTKIs) (Nakamura et al, 2001).…”
mentioning
confidence: 99%